Políticas públicas de saneamento básico: um estudo de caso no município de Ananindeua, estado do Pará, a partir da lei nº 11.445/07 - EUGENIO, Dieri do Socorro da Silva (Universidade Federal do Pará, 2019)
This research sought to analyze the Municipal Public Policy of Basic Sanitation in Ananindeua (PA), specifically regarding the compliance with the guideline related to the exercise of title, article 9 of Law n. 11.455/2007, known as the National Sanitation Law (NSL), which establishes the requirements that must be observed by the service holder in the formulation and implementation of the respective policy. Considering the low performance of Ananindeua in the sanitation service offer (second last placement in the National Ranking in 2018), it was assumed that, even though the existence of a legal framework to guarantee the provision of a quality service, it is necessary to adopt an adequate policy, able to meet the demand and promote the universalization of access in the municipality. The method of case study and qualitative approach was adopted as strategy. The technical procedures for collecting data were the bibliographical, documentary and field research, carried out through semi-structured interviews, with actors and institutions involved in this public policy in the municipality. There were several weaknesses in meeting the following requirements: planning and municipal plan for basic sanitation; regulation and inspection of sanitation services; establishment of the rights and duties of users; participation and social control and municipal information system on sanitation; it was concluded that the service holder does not adequately comply with the guidelines established in the NSL, demonstrating the damages resulting from this context and making recommendations for the improvement of sanitation services in Ananindeua, as required by Law n. 11.445/2007.